Comparing Phytosociological Attributes for Trees Outside Forest and Enrichment Plantation: Strategies for Sustainable Urban Forest Management - Ghosh, Paromita (Indian Forester, 2025)
Trees Outside Forests (TOF) and Enrichment Plantations (EP) are strategies used in urban forestry management to increase green cover and address various ecological issues such as deforestation. The Government of India has initiated the promotion of TOF and EP to address resource demands and provide various ecosystem services in urban and semi-urban areas. This study examined Anand Van (an urban TOF) in Dehradun and Nanda Van (an EP) in Almora, focusing on their ecological attributes that reflect the suitability of the two forest management systems to address environmental challenges. Phytosociological analysis revealed that broad-leaved Mallotus philippinensis was the dominant species in Anand Van, whereas needleleaved Pinus roxburghii was the dominant species in Nanda Van. The importance value index (IVI) indicates higher ecological significance for TOF due to their more diverse mixed vegetation and natural regeneration, resulting in higher biodiversity compared to EP. Recognizing the complementarity of these strategies and spreading awareness among stakeholders is essential for sustainable urban forest management. A location-specific mixed-method approach of both strategies can help improve urban greenery and ecosystem services and augment business strategy through natural resource management.